Good governance principles and academic administration behavior of educational personnel at Sukhothai Vocational College - Sritawet, Charinthip; Wiwatchankit, Sopee; Kumhom, Naitawan (RATANABUTH JOURNAL, 2022)
This research aims to 1) To study the level of good governance 2) to study the level of academic administration behavior 3) to study the relationship of good governance and academic administration behavior of educational personnel at Sukhothai Vocational College This population is the population studied in this study, which is 72 educational personnel. The instrument used was a questionnaire. data analysis Finding Percentage, Mean, and Standard Deviation and find a relationship by Pearson’s product correlation coefficient. The results of the research found that most of the respondents were female, 58 people aged 30-40 years old, 48 people with bachelor's degree, 64 people with less than 10 years of work experience, 53 people.1) Overall good governance of educational personnel at Sukhothai Vocational College is at a high level. When considering each aspect, it was found that the first place was the rule of law, followed by the moral principle. The principle of transparency the principle of participation Responsibility And the last is the value principle.2) Academic administration behaviors of educational personnel at Sukhothai Vocational College as a whole at a high level When considering each item, it was found that the first place was in the field of Academic Services and the Library, followed by the department of the subjects offered. in the field of curriculum development work Measurement and evaluation work in the field of vocational education in the bilateral system and the final ranking is Teaching media work 3) The relationship of good governance principles and academic administration behaviors of educational personnel at Sukhothai Vocational College, as a whole, had a positive correlation at a moderate level. statistically significant at 0.01 level.